Antiviral Properties of Water Extracts of Mycelium Inonotus rheades (Pers.) P. Karst. (1882) against the Virus of Tick-Borne Encephalitis Virus in vitro - M. A. Khasnatinov; T. G. Gornostai; I. S. Solovarov; M. S. Polyakova; G. A. Danchinova; G. V. Borovskii (Acta Biomedica Scientifica)
Background. Tick-borne encephalitis virus is dangerous and widespread pathogen that is transmitted to humans through the bites of hard ticks. Wild fungi, such as xylotrophic basidiomycetes, are widely used in traditional medicine to treat the infectious diseases and are promising natural sources of new antiviral agents. It was previously shown that aqueous extracts from the mycelium of the Inonotus rheades (Pers.) P. Karst. (1882) fungus exhibit significant antiviral activity against tick-borne encephalitis virus, however, the mechanisms of this activity remain unclear.Aim. To analyze the relationship between the virucidal properties of I. rheades extract and the substrate on which the cultivation was carried out.Materials and methods. The mycelium was grown either in a standard liquid medium with wort or on wooden disks from birch. Extracts of water-soluble polysaccharides were prepared from both mycelium samples. The concentration of infectious tick-borne encephalitis virus was determined using the method of titration of plaque-forming components (PFU). Approximately 30 000 PFU of tick-borne encephalitis virus was mixed with an equal volume of corresponding I. rheades extract at concentration of 8 mg/mL and incubated for 30 min at 37 °C. Afterwards, the residual infectivity of tick-borne encephalitis virus was determined using the identical virus sample incubated with sterile water as a reference.Results. It was found that treatment of tick-borne encephalitis virus with extracts from I. rheades mycelium resulted in inhibition of the infectivity of the virus in the cell culture. However, the same strain of I. rheades, grown on medium with wort, did not exhibit antiviral properties.Conclusions. Virucidal substances are likely to be not the main metabolites of the mycelium of I. rheades, but are rather metabolized wood polysaccharides. Further research is needed to more accurately identify the active ingredients and assess their antiviral activity.